2005
DOI: 10.1381/0960892054222876
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related Differential Gene Expression in the Visceral Adipose Tissue

Abstract: Differential gene expression in the adipose tissue of morbidly obese patients includes genes related to lipid and glucose metabolism, membrane transport, and genes promoting the cell cycle. These findings are a first step toward clarifying the molecular pathogenesis of obesity and identifying potential targets for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 18 publications
5
55
0
1
Order By: Relevance
“…However, the impact of type 2 diabetes has not been examined, and we are the first to report a comparison of gene expression profiles in human subcutaneous and visceral fat of nonobese, obese nondiabetic, and type 2 diabetic subjects. A previous published gene expression profiling on human visceral adipose tissue described the prominent impact of morbid obesity on glycolysis enzymes, oxysterol biosynthesis and signaling, ATP-binding transporters, and solute carriers (37). The absence of a clear impact on electron transport chain genes in that study supports downregulated expression of these genes being directly associated with type 2 diabetes, rather than obesity in general.…”
Section: Discussionmentioning
confidence: 55%
“…However, the impact of type 2 diabetes has not been examined, and we are the first to report a comparison of gene expression profiles in human subcutaneous and visceral fat of nonobese, obese nondiabetic, and type 2 diabetic subjects. A previous published gene expression profiling on human visceral adipose tissue described the prominent impact of morbid obesity on glycolysis enzymes, oxysterol biosynthesis and signaling, ATP-binding transporters, and solute carriers (37). The absence of a clear impact on electron transport chain genes in that study supports downregulated expression of these genes being directly associated with type 2 diabetes, rather than obesity in general.…”
Section: Discussionmentioning
confidence: 55%
“…Park and Lee (29) reported that OM fat reduction in obese patients induces greater beneficial effects on parameters of the metabolic syndrome than SC fat reduction. Recent studies have shown a differential gene expression in the OM adipose tissue of morbidly obese patients, in particular for genes related to lipid and glucose metabolism, compared with lean individuals (30). We found that AM expression in OM tissue correlates with body composition, systolic blood pressure and some biochemical components involved in the metabolic syndrome.…”
Section: Lean Population (Nz9)mentioning
confidence: 49%
“…Finally, glucose phosphate isomerase (GPI) is another glycolytic enzyme that is responsible for the conversion of glucose-6-phosphate to fructose-6-phosphate. It has been reported that glycolytic genes, such as GPI and ENO3, are downregulated in the visceral adipose tissue of morbidly obese patients compared with nonobese counterparts (6). Increased GPI expression in subcutaneous fat in response to NBC supplementation is consistent with a myogenic induction of adipose tissue, as GPI is highly expressed in skeletal muscle (9).…”
Section: Niacin-bound Chromium In Obesitymentioning
confidence: 86%